Dampak Dunia Digital Terhadap Kesejahteraan Masyarakat di Indonesia - Adya Utami Syukri; Megawaty Megaway (Movere Journal, 2025)
This study aims to analyze the influence of digital development on public welfarein Indonesia, as measured by the Human Development Index (HDI). The digital world isrepresented by three main variables: internet access, internet infrastructure, and internet users.The method used in this study is panel data analysis with the Common Effect Model (CEM), FixedEffect Model (FEM), and Random Effect Model (REM) approaches, using secondary data from34 provinces in Indonesia during the period 2018–2021. The results of the Chow and Hausmantest indicate that the most appropriate model is the Fixed Effect Model (FEM). The FEMestimation results indicate that the variables of internet access and internet infrastructure have apositive and significant effect on the HDI, while the variable of internet users does not show asignificant effect. This indicates that the availability of digital access and infrastructure plays acrucial role in driving human development, while the number of users has not had a significantimpact without adequate digital literacy support.